IgM and IgG Antibodies Status in Suspected Patients of Covid-19 in Khyber Pakhtunkhwa, Pakistan (Medical Forum Monthly, 2021)
Objective: To implement a new screening method in Pakistan's Khyber Pakhtunkhwa (KPK) province, increase testing capability, alleviate the burden on the PCR facility, and learn more about the infected population's herd immunity.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Biotechnology, Real Time PCR Laboratory Dabgari garden Peshawar from April, 2020 to June, 2020.Materials and Methods: A total of 200 individuals between the ages of 20 and 60 were included in the study. Immunochromatographic Technique was used to screen both of these patients for IgM and IgG levels (AMP, Australian).Results: Antibodies were detected in 92 (46%) of the subjects (IgM and IgG). IgM and IgG positive patients reported for 7 (8%) and 85 (92%) of the 92 positive patients, respectively. There were 72 (51%) male and 20 (3%) female positive subjects, respectively. The 20-30 age group was the most affected, followed by the 30-40 age group, and the >60 age group was the least affected. Temperature was the most common symptom associated with suspicious subjects (85%), followed by body aches (80%), dry cough (77%) and sore throat (70%).Conclusion: The prevalence of antibodies, IgM, and IgG positivity was very high (46%) among the suspected patients, and the most affected age group was 20-30, with temperature symptoms being the most common.